Методика розрахунку функціональних поверхонь насадок для фонтанів із заданими характеристиками - Гавриленко, Євген Андрійович; Havrilenko, Yevhen; Антонова, Галина Володимирівна; Antonova, Halyna; Чаплінський, Андрій Петрович; Chaplinskyi, Andriy; Спірінцев, Д. В. (Одеса : Видавничий дім “Гельветика”, 2024)
UA: Проведено аналітичний огляд конструктивних особливостей фонтанних насадок. Встановлено, що технічні огріхи при їх виготовленні перешкоджають формуванню чіткої геометрії водного малюнка, спричиняють надмірне розбризкування, збільшують енерговитрати насосного обладнання та провокують виникнення зайвого шуму. Такі дефекти призводять до невідповідності виробу проектним характеристикам та ускладнюють його подальшу експлуатацію. Для подолання вказаних проблем розроблено математичний підхід до обчислення параметрів профілю насадки. В основі методу лежить побудова робочої поверхні шляхом інтерполяції дискретно представлених кривих (ДПК) із застосуванням серединних перпендикулярів. Паралельно з теоретичною методикою створено програмний комплекс для автоматизованого проектування деталей у середовищі CAD-системи AutoCAD. /// EN: The primary goal of any fountain installation is to enable the dynamic motion of water. To build visually appealing compositions, it is essential to have an adequate supply of water, which can be sourced from natural or man-made reservoirs, as well as pools. The selection of a water storage solution is closely linked to the specific fountain category and the intended visual outcomes. These outcomes vary from gentle, smooth flows and small creeks to energetic waterfalls, high altitude vertical jets, or sophisticated spatial arrangements created by multiple specialized nozzles. When engineering the hydraulic network and choosing pump equipment, it is vital to account for the precise pressure and flow rate requirements of each nozzle. The most suitable material for the production of hydraulic nozzle components is specialized copper-based alloys. Such materials demonstrate high resistance to corrosion, ensuring that no surface cavities develop during long-term exposure to water, while also being cost-effective and easy to machine or polish with precision. Once the nozzle type is selected based on the desired visual effect, focus must be placed on its operational range, how it reacts to water level changes, the amount of noise it produces, and its stability under wind conditions, which affects the splash radius. An investigation into fountain nozzle architectures revealed that substandard manufacturing prevents the creation of accurate water geometries and leads to excessive splashing and increased energy consumption by the pump. Furthermore, such nozzles often fail to meet their specified technical data, causing acoustic issues and operational difficulties that hinder the full realization of the original fountain design. To resolve these technical gaps, a mathematical approach for determining nozzle profile points has been introduced, utilizing surface construction via Discrete Point Curve interpolation and the method of perpendicular bisectors. Along with this geometric modeling framework, a software tool has been created to facilitate automated design within the AutoCAD environment.
Methodology for calculating the functional surfaces of nozzles for fountains with specified characteristics
Keywords: експлуатаційний діапазон; акустичне навантаження; розбризкування; дискретно представлена крива (ДПК); супроводжуюча ламана лінія (СЛЛ); інтерполяційна модель; серединні перпендикуляри; кути суміщення; осциляція; ідентичність згущення; working range; noise level; splash formation; discretely represented curve (DRC); accompanying broken line (ABL); interpolation; median perpendiculars; alignment angles; oscillation; condensation identity